Godmanhood vs Mangodhood: An Eastern Orthodox Response to Transhumanism. (May 2019) - Gallaher, Brandon
This article distances the classic Patristic teaching of Eastern Orthodoxy on theosis from the pseudo-religious ideology of transhumanism. By appealing to the Silver Age of Russian theologians a century ago, today's transhumanist vision is dubbed Mangodhood, an idolatrous construction of a technological Tower of Babel. In contrast, the classical Orthodox teaching of deification or theosis relies on the spiritual grace of the true God, rendering the true goal of religion to be Godmanhood.